(untitled) (Journal of Engineering, 2014)
The main objective of present work is to describe the feasibility of friction stir welding (FSW) for joining of low carbon steel with dimensions (3 mm X 80 mm X 150 mm). A matrix (3×3) of welding parameters (welding speed and tool rotational speed) was used to see influence of each parameter on properties of welded joint .Series of (FSW) experiments were conducted using CNC milling machine utilizing the wide range of rotational speed and transverse speed of the machine. Effect of welding parameters on mechanical properties of weld joints were investigated using different mechanical tests including (tensile and microhardness tests ). Micro structural change during (FSW) process was studied and different welding zones were investigated using optical microscope. The stir welding experiments conducted that show the low carbon steel can be welded using (FSW) process with maximum welding efficiency (100.02%) in terms of ultimate tensile strength using best result of welding parameters (700 RPM, 25 mm/min, tool rotational speed and welding speed respectively and 0.2 mm plunging depth of welding tool) ,there is afirst time that we obtain the efficiency reach to 100.02 % to weld this type of low carbon steel by FSW. The corrosion resistance was measure which is the new test on the welding by this way and we obtained different result from the result on traditional welding processes and the result that obtained show the corrosion resistance for this welding plate better than the base metal. Maximum temperature has been calculated numerically by using the ANSYS program. The obtained peak temperature is 1102°C, A percentage minimum of the melting point .